건물에너지 저감을 위한 향별 슬랫형 블라인드의 최적각도 제어 알고리즘 산출 - 권혁주(Kwon, Hyuk-Ju); 이금호(Lee, Keum-Ho); 이광호(Lee Kwang Ho) (KIEAE Journal, 2017)
Purpose: Most modern office buildings adopt the curtain wall system in order to provide occupants with the sense of openness and high-technology, which requires large window area. As a result, the amount of solar radiation increases, negatively affecting cooling load during the summer and increasing energy costs. However, the performance of window itself is not sufficiently controllable parameter to control thermal comfort and solar radiation. Therefore, a shading device such as venetian blind is required to control them and thus a variety of studies have been performed thus far. So, the purpose of this study is to improve the performance of blind through the development of blind control algorithm. Method: Among various input variables for the control of venetian blinds, the vertical solar radiation has been selected in this study as the primary input variable and the optimal control algorithm for venetian blinds were developed for each window orientation. Result: The developed optimal control algorithm has a positive effect on building energy savings.